The Perceived Value of Passive Animal Health Surveillance: The Case of Highly Pathogenic Avian Influenza in Vietnam. (3rd July 2015) - Delabouglise, A.; Antoine‐Moussiaux, N.; Phan, T. D.; Dao, D. C.; Nguyen, T. T.; Truong, B. D.; Nguyen, X. N. T.; Vu, T. D.; Nguyen, K. V.; Le, H. T.; Salem, G.; Peyre, M.
Summary: Economic evaluations are critical for the assessment of the efficiency and sustainability of animal health surveillance systems and the improvement of their efficiency. Methods identifying and quantifying costs and benefits incurred by public and private actors of passive surveillance systems (i.e. actors of veterinary authorities and private actors who may report clinical signs) are needed. This study presents the evaluation of perceived costs and benefits of highly pathogenic avian influenza (HPAI) passive surveillance in Vietnam. Surveys based on participatory epidemiology methods were conducted in three provinces in Vietnam to collect data on costs and benefits resulting from the reporting of HPAI suspicions to veterinary authorities. A quantitative tool based on stated preference methods and participatory techniques was developed and applied to assess the non‐monetary costs and benefits. The study showed that poultry farmers are facing several options regarding the management of HPAI suspicions, besides reporting the following: treatment, sale or destruction of animals. The option of reporting was associated with uncertain outcome and transaction costs. Besides, actors anticipated the release of health information to cause a drop of markets prices. This cost was relevant at all levels, including farmers, veterinary authorities and private actors of the upstream sector (feed, chicks and medicine supply). One benefit associated with passive surveillance was the intervention of public services to clean farms and the environment to limit the disease spread. Private actors of the poultry sector valued information on HPAI suspicions (perceived as a non‐monetary benefit) which was mainly obtained from other private actors and media.